Covid-19 and Literary Resistance in Pakistan: A Feminist Analysis of The Stained-Glass Window - Langah, Dr. Nukbah Taj (Journal of Research in Humanities, 2023)
This paper explores the stories of women impacted by COVID-19 and narrated by Pakistani writers. The discussion is primarily based on flash fiction from a recent anthology entitled, The Stained-Glass Window (2020). I critically analyse selected short stories in the context of the cultural taboos (such as, patriarchy, sexism, biological essentialism), historically thrust upon Pakistani women. The analysis is based on the lives of the female protagonists (irrespective of their age, class, race, ethnicity, or religious differences) and their experiences during multiple lockdowns in Pakistan. This textual analysis is presented in the light of Kate Millet’s theoretical framework (Millet 1990) to contend that these Pakistani writers resist the deepening sexual politics through fictional characters evidently strengthening the contemporary feminist resistance emerging from Pakistan. The paper is primarily concerned with the issues of sexual politics (Millet 24), ‘internal colonization’ and gender-based power dynamics (25) experienced by women during the pandemic in the light of feminist resistance in Pakistan.